Relationship between parafunctional habits and clinical characteristics of the temporomandibular joint - Peláez, Alina Noelia (2018)
Objective: Relate the parafunctional habits and the clinical characteristics of the temporomandibular joint. Methods: 125 patients aged 18 to 50 years were evaluated, the presence of joint noise was diagnosed, clinical characteristics such as restriction of the mouth opening, irregularity in the movement of opening and closing, pain of chewing muscles, joint pain, wear facets and parafunctional habits such as bruxism, unilateral chewing and biting of objects. Results: 34% of the patients presented noise in the temporomandibular joint. The bruxism, presented significant relationship with restriction of the mouth opening (p=0.0013), irregularity in the movement of opening and closing(p=0.0065), muscle pain (p<0.001), wear facets (p=0.0048), and no relationship was found with joint pain (p=0.0489). Unilateral mastication was significantly related to all clinical characteristics evaluated, mouth opening restriction (p=0.0040), irregularity in opening and closing movement (p<0.001), muscle pain (p=0.0015), joint pain (p=0.003), wear facets (p=0.0015). The bite of objects was not related to the clinical characteristics evaluated. Conclusions: Noises at the level of the temporomandibular joint are frequent, being the click the most frequent. The bruxism, presented significant relationship with the restriction of the oral opening, the irregularity in the movement of opening and closing, muscle pain, wear facets, and no relation was found with joint pain. The unilateral mastication was significantly related to all the clinical characteristics and the bite of objects was not related to the clinical characteristics of temporomandibular dysfunction studied.